LEGAL PROTECTION RELATED TO THE DENSITY RIGHTS IN TERMS OF REWARDED IN CORRECTIONAL INSTITUTION - Lily Faradina; Kadek Wiwik Indrayanti (UNISSULA, 2018)
The rights of prisoners have been explicitly regulated in Act No.12 of 1995 on Corrections. The law therein outlines 13 (thirteen) rights reserved for a prisoner while in a Penitentiary. The right to get a wage or premium for the work done is a right that is often neglected in practice in the correctional institution located in our country. This happens because of the stigma of the people who still tend to assume that a prisoner is a party that deserves to be treated arbitrarily because of the crime he has committed. It is this kind of thinking that ultimately also affects officials or prison officers who end up treating incendiary people like humans who are unfit to accept the rights that have been provided by the state. Many inmates are employed in penitentiaries who are not paid for by their employers. If this continues to be done then the purpose of punishment will actually violate human rights inherent in the Prisoners as human beings. However, prisoners must also be protected by their rights as human beings.